Implementation of Adult Learning by Computer Course Instructor in the Training Course Agency (LKP) Equivalency Education Program - Reska Ilda Misa Putri; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the reality in the field which shows that adult learning that must prioritize the characteristics of the assumption of adult learning is a program carried out by computer course instructors at the Kurnia Computer Training Course Institute (LKP). In the course of the course, learning is usually directed at adults at the Kurnia Computer Training Course Institute (LKP) which is categorized as quite applied. This can be seen from the learning provided by the instructor to adults well and the supporting facilities and infrastructure. The purpose of this study was to find out (1) a description of the application of the assumptions of adult learning experiences in the implementation of computer courses by instructors (2) an overview of the application of the assumptions of adult self-concept in the implementation of computer courses (3) an overview of the application of the assumption of adult learning readiness in the implementation of computer courses by instructor. This type of research is descriptive research which was carried out at the Kurnia Computer Pesisir Selatan Training Course Institute (LKP). The approach used in this research is quantitative. The population of the study was the participants of the computer course of the Kurnia training course institution (LKP) which amounted to 15 people. The sample amounted to 15 people using saturated sampling technique for sampling, meaning that the sample was taken as a whole, namely 100%. Techniques in data collection using written statements (questionnaires) and data collection tools in the form of a list of statements. The data analysis technique uses the percentage formula. The results of this study indicate that: (1) The description of the application of adult learning assumptions by computer course instructors at the Pesisir Selatan computer course and training institute (LKP) seen from the sub-variables of experience is categorized as quite applied. (2) The description of the application of adult learning assumptions by computer course instructors at the Kurnia Pesisir Selatan computer course and training institution (LKP) seen from the sub-variables of self-concept is categorized as quite applied. (3) The description of the application of adult learning assumptions by computer course instructors at the Kurnia Pesisir Selatan computer course and training institution (LKP) seen from the sub-variables of learning readiness is categorized as quite applied. It is suggested to other researchers to develop this research with different variables so that it can deepen the study of the assumptions of adult learning.